A new species of the rare cleptoparasitic bee genus Ptilocleptis (Hymenoptera: Halictidae) from Mexico - Quintos-Andrade, Gerardo; Valenzuela-González, Jorge E. (Zootaxa, 2026)
Sphecodini is a tribe with worldwide distribution, exhibiting a distinctive western hemispherical fauna composed of six genera and approximately 138 species. Among these genera, Ptilocleptis is unique due to its distinctive synapomorphies and its rarity in entomological collections. In this study, Ptilocleptis mictlan Quintos-Andrade sp. nov. is described from Mexico, new distributional records of P. tomentosa Michener within Mexico are presented, and an identification key to the species of Ptilocleptis is provided. The diversity of Ptilocleptis, its potential hosts, and most important diagnostic characters to delimit species are discussed.